Method for manufacturing flexible substrate
By forming a base metal layer containing chromium and a copper conductor layer on the surface of the polyimide film of the flexible substrate, and adjusting the chromium distribution by superheated water vapor treatment, the problem of the decrease in heat peel strength of the flexible substrate at high temperature is solved, and cost reduction and performance improvement are achieved.
Patent Information
- Application Number
- CN202411876196.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-22
- Filing Date
- 2019-09-16
- Publication Date
- 2025-03-25
AI Technical Summary
The conventional flexible substrate has a problem of decreasing heat peel strength at high temperatures, and the cost of suppressing this reduction is relatively high.
A polyimide film is used as a substrate and a base metal layer is formed on the surface, which contains a metal layer containing chromium, and the weight percentage of chromium is higher in the first metal layer to suppress the diffusion of copper and form a copper conductor layer thereon. The distribution of chromium is adjusted by superheated water vapor treatment to ensure that the chromium content in the first metal layer is high.
The decrease in heat-resistant peel strength is effectively suppressed, while the manufacturing cost of flexible substrates is reduced, and the peel strength at high temperatures is maintained.
Smart Images

Figure CN119697903A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of September 16, 2019, application number 201910871042.5, and invention name “Flexible Substrate”. Technical Field
[0002] The present invention relates to a flexible substrate, and more particularly to a flexible substrate having excellent heat resistance. Background Art
[0003] In liquid crystal panels, notebook computers, digital cameras, mobile phones, etc., many types of flexible wiring substrates are used, which are obtained by covering a heat-resistant resin film with a metal film. Among these flexible wiring substrates, resin films with metal films formed on one or both sides of a heat-resistant resin film are used in large quantities. In this specification, these resin films with metal films are sometimes referred to as "flexible substrates".
[0004] As a method for manufacturing such a flexible substrate, conventionally known are a method of manufacturing by attaching a metal foil to a resin film by an adhesive (a method for manufacturing a three-layer substrate), a method of manufacturing by coating a thermosetting resin solution on a metal foil and drying it (a coating method), a method of manufacturing by attaching a thermoplastic resin film to a metal foil and performing thermocompression bonding (a lamination method), and a method of manufacturing by forming a metal film on a resin film by a vacuum film forming method, a vacuum film forming method, and a wet film forming method (a metallization method), etc. In addition, the vacuum film forming method of the metallization method includes a vacuum evaporation method, a sputtering method, an ion plating method, an ion beam sputtering method, and the like.
[0005] Here, it is known that among vacuum film forming methods, sputtering generally has excellent adhesion, but the peel strength measured after the substrate is heated to 150° C. in the atmosphere and held for 168 hours (hereinafter sometimes referred to as heat-resistant peel strength) decreases.
[0006] Regarding the flexible substrate that suppresses the decrease in the heat-resistant peel strength, Patent Document 1 discloses a method of forming a conductor layer on a polyimide insulating layer by sputtering a chromium layer on a polyimide insulating layer and then sputtering copper as a metal spraying method. In addition, Patent Document 2 discloses a material for a flexible circuit substrate formed by stacking a first metal film and a second metal film in this order on a polyimide film, wherein the first metal film is formed by sputtering with a copper-nickel alloy as a target, and the second metal film is formed by sputtering with copper as a target. Furthermore, Patent Document 3 discloses a two-layer copper polyimide substrate obtained by modifying the surface of a polyimide film, and Patent Document 4 discloses a metal-coated polyimide resin substrate obtained by modifying the surface of a polyimide resin film.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent document 1: Japanese Patent Application Laid-Open No. 2-98994.
[0010] Patent document 2: Japanese Patent No. 3447070.
[0011] Patent document 3: Japanese Patent Application Publication No. 2007-318177.
[0012] Patent document 4: International Publication No. 2010 / 098236. Summary of the invention
[0013] In Patent Documents 1 and 2, in order to suppress the decrease in heat-resistant peel strength, a metal layer of chromium or nickel-copper is formed on the surface of a polyimide film by sputtering. However, in the flexible substrates obtained from these documents, the decrease in heat-resistant peel strength is not sufficiently suppressed. In addition, in Patent Documents 3 and 4, although the decrease in heat-resistant peel strength is suppressed by modifying the surface of the polyimide film before forming a metal layer on the polyimide film, it cannot be said that the decrease in heat-resistant peel strength is sufficiently suppressed, and there is a problem of cost in the process of plasma treatment and the like for modifying the surface of the polyimide film.
[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a flexible substrate capable of reducing the overall manufacturing cost of the flexible substrate while suppressing a decrease in heat-resistant peel strength.
[0015] The flexible substrate of the first invention is characterized in that it includes a polyimide film, a base metal layer formed on the surface of the polyimide film, and a copper conductor layer formed by overlapping the base metal layer, wherein the base metal layer includes a metal layer containing chromium, the metal layer containing chromium has a first metal layer connected to the polyimide film, and a second metal layer located on the first metal layer in an overlapping manner, and the weight percentage of chromium in the first metal layer is greater than the weight percentage of chromium in the second metal layer.
[0016] The flexible substrate of the second invention is characterized in that, in the first invention, the metal layer containing chromium is a nickel-chromium alloy layer.
[0017] According to the first invention, the base metal layer formed on the surface of the polyimide film includes a metal layer containing chromium, and in the metal layer containing chromium, the weight percentage of chromium in the first metal layer in contact with the polyimide film is greater than the weight percentage of chromium in the second metal layer, thereby suppressing the diffusion of copper into the first metal layer. Since the heat-resistant peel strength is reduced by the decomposition of the polyimide film by copper, the reduction in the heat-resistant peel strength can be suppressed by suppressing the diffusion of copper into the first metal layer. In addition, since it is relatively easy to make the weight percentage of chromium in the first metal layer greater than the weight percentage of chromium in the second metal layer, the reduction in the heat-resistant peel strength can be suppressed while reducing the manufacturing cost of the flexible substrate.
[0018] According to the second invention, the metal layer containing chromium is a nickel-chromium alloy layer. Therefore, since the nickel-chromium alloy is easily available, it is possible to suppress a decrease in heat-resistant peel strength at a lower cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a partially enlarged cross-sectional view of the flexible substrate according to the first embodiment of the present invention.
[0020] Figure 2 It is a cross-sectional view of the flexible substrate according to the first embodiment of the present invention.
[0021] Figure 3 TEM element mapping measurement diagrams of the flexible substrate according to the first embodiment of the present invention. (Figure A) is a diagram showing the distribution state of the Cr element after the superheated water vapor treatment. (Figure B) is a diagram showing the distribution state of the Cr element before the superheated water vapor treatment. (Figure C) is a diagram showing the distribution state of the Cu element after the superheated water vapor treatment. (Figure D) is a diagram showing the distribution state of the Cu element before the superheated water vapor treatment.
[0022] The symbols are explained as follows:
[0023] 10: Flexible substrate.
[0024] 11: Polyimide film.
[0025] 12: Base metal layer.
[0026] 13: Copper conductor layer.
[0027] 14: Metal layer containing chromium.
[0028] 14a: First metal layer.
[0029] 14b: Second metal layer. DETAILED DESCRIPTION
[0030] Next, the embodiments of the present invention are described based on the drawings. However, the embodiments shown below are examples of the flexible substrate 10 for embodying the technical concept of the present invention, and the flexible substrate 10 of the present invention is not particularly limited thereto. It should be noted that the size or positional relationship of the components shown in the drawings may be exaggerated for the purpose of clear description.
[0031] (First Embodiment)
[0032] Figure 2 FIG. 4 is a cross-sectional view of a flexible substrate 10 according to a first embodiment of the present invention. Figure 2 As shown in the figure, the flexible substrate 10 of the present invention comprises a polyimide film 11, a base metal layer 12 formed on the surface of the polyimide film 11, and a copper conductor layer 13 formed by overlapping the base metal layer 12. The base metal layer 12 is composed of, for example, a metal layer 14 containing chromium and a base copper layer 15 provided on the side of the polyimide film 11. It should be noted that in the present embodiment, the base metal layer 12 is formed on one side of the polyimide film 11, but it is not particularly limited to this. The base metal layer 12 is formed on both sides of the polyimide film 11, which also belongs to the flexible substrate 10 of the present invention.
[0033] Figure 1 It is shown in Figure 2 In the present embodiment, the chromium-containing metal layer 14 of the base metal layer 12 is composed of a first metal layer 14a in contact with the polyimide film 11 and a second metal layer 14b located on the first metal layer 14a in an overlapping manner. In addition, in the flexible substrate 10 of the present invention, the weight percentage of chromium in the first metal layer 14a is greater than the weight percentage of chromium in the second metal layer 14b.
[0034] In the base metal layer 12 formed on the surface of the polyimide film 11, the weight percentage of chromium in the first metal layer 14a in contact with the polyimide film 11 is greater than the weight percentage of chromium in the second metal layer 14b, thereby suppressing the diffusion of copper into the first metal layer 14a as described below.
[0035] One of the reasons why the heat-resistant peel strength of the flexible substrate 10 decreases is that the polyimide film 11 is decomposed by copper. That is, if the copper with high conductivity can be prevented from directly contacting the polyimide film 11, the heat-resistant peel strength will be increased. Since at least a part of the base metal layer 12 is a metal layer 14 containing chromium in this embodiment, specifically a nickel-chromium alloy layer, it is possible to prevent copper from contacting the polyimide film 11. However, if only the metal layer 14 containing chromium is formed, when the temperature of the flexible substrate 10 increases, copper gradually diffuses in the metal layer 14 containing chromium and becomes in contact with the polyimide film 11.
[0036] Therefore, a layer rich in chromium, that is, the first metal layer 14a, is provided on a part of the metal layer 14 containing chromium. When the temperature of the flexible substrate 10 rises, copper is combined with oxygen in the metal layer 14 containing chromium and diffuses in the metal layer 14 containing chromium. If the layer where oxygen combines with chromium, that is, the first metal layer 14a rich in chromium, exists, the diffusion of copper is suppressed by the first metal layer 14a even if the temperature of the flexible substrate 10 rises, and the decrease in heat-resistant peel strength can be suppressed.
[0037] In addition, a method of making the weight percentage of chromium in the first metal layer 14a larger than the weight percentage of chromium in the second metal layer 14b is described below, but because this method can be implemented relatively easily, it is possible to suppress the decrease in heat-resistant peel strength while reducing the manufacturing cost of the flexible substrate 10.
[0038] In addition, in the flexible substrate 10 of the present invention, the base metal layer 12 includes a metal layer 14 containing chromium, that is, a nickel-chromium alloy layer, and the nickel-chromium alloy layer is preferably composed of a first metal layer 14a and a second metal layer 14b. Since nickel-chromium alloys are easily available, the decrease in heat-resistant peel strength can be suppressed more cheaply.
[0039] (Polyimide film 11)
[0040] The polyimide film 11 used in the flexible substrate 10 of the present embodiment is a film-shaped insulator, such as Kapton (registered trademark) 100EN film manufactured by Toray DuPont and UPILEX (registered trademark) 25SGA manufactured by Ube Industries.
[0041] (Base Metal Layer 12)
[0042] The base metal layer 12 constituting the flexible substrate 10 of the present embodiment is directly formed on the surface of the polyimide film 11. Preferably, the base metal layer 12 is formed by including a metal layer 14 containing chromium and a base copper layer 15. The metal layer 14 containing chromium is a nickel-chromium alloy in the present embodiment, but other metals selected from at least one of chromium and chromium oxide can also be used. Preferably, these base metal layers 12 are formed by sputtering of dry plating. It should be noted that the formation of the base metal layer 12 can also be performed by vacuum evaporation or ion plating.
[0043] The metal layer 14 containing chromium has better adhesion than the synthetic resin constituting the polyimide film 11. In addition, the base copper layer 15 has high conductivity. By constituting the base metal layer 12 as two layers, the adhesion between the base metal layer 12 and the polyimide film 11 is improved, and the conductivity is improved, and dry plating of the copper conductor layer 13 provided to overlap the base metal layer 12 can be easily performed.
[0044] The thickness of the metal layer 14 containing chromium is preferably not less than 50 angstroms and not more than 500 angstroms, and the thickness of the underlying copper layer 15 is preferably not less than 500 angstroms and not more than 5000 angstroms.
[0045] When the thickness of the metal layer 14 containing chromium is less than 50 angstroms, problems with adhesion are likely to occur in the subsequent processing steps. In addition, when it is thicker than 500 angstroms, it becomes difficult to remove nickel or chromium during wiring processing, and cracks or warping are likely to occur on the metal layer 14 containing chromium. At this point, problems with adhesion between the polyimide film 11 and the base metal layer 12 are likely to occur. In addition, when the thickness of the base copper layer 15 is less than 500 angstroms, the defect reduction effect caused by pinholes becomes small, and there is a possibility of causing poor power supply during wet plating performed later. In addition, when it exceeds 5000 angstroms, cracks or warping are likely to occur on the base copper layer 15. At this point, problems with adhesion between the polyimide film 11 and the base metal layer 12 are likely to occur.
[0046] The weight percentage of chromium in the chromium-containing metal layer 14 is preferably 12% or more and 50% or less. With such a configuration, the reliability of suppressing the diffusion of copper into the first metal layer 14a can be improved.
[0047] When the weight percentage of chromium is less than 12%, chromium cannot be sufficiently moved to the first metal layer 14a, and the movement of copper cannot be sufficiently suppressed. In addition, when the weight percentage of chromium is more than 50%, the cost of sputtering increases.
[0048] (Copper conductor layer 13)
[0049] The copper conductor layer 13 constituting the flexible substrate 10 of the present embodiment is directly formed on the surface of the base metal layer 12. When the flexible substrate 10 of the present embodiment is made into a flexible wiring substrate by a semi-additive method, the thickness of the copper conductor layer 13 is about 2 μm. This is because the operability of the flexible substrate 10 becomes good. In addition, when the flexible substrate 10 of the present embodiment is made into a flexible wiring substrate by a subtractive method, the thickness of the copper conductor layer 13 is about 8 μm. It should be noted that the flexible substrate 10 of the present invention is not limited to these thicknesses. The wet plating implemented in the manufacturing method of the flexible substrate 10 of the present embodiment is a well-known electroplating.
[0050] (Superheated water vapor treatment)
[0051] In the flexible substrate 10 of the present embodiment, after forming the copper conductor layer 13, a superheated water vapor treatment is performed by spraying superheated water vapor. By performing the superheated water vapor treatment, the chromium-containing metal layer 14 constituting the base metal layer 12 is configured such that the weight percentage of chromium in the first metal layer 14a is greater than that in the second metal layer 14b. In addition, in the present embodiment, the chromium-containing metal layer 14 is configured such that the chromium content of the first metal layer 14a is increased by the superheated water vapor treatment, but, for example, by heating in a vacuum furnace, it is also possible to configure the first metal layer 14a to have an increased oxygen content.
[0052] The temperature of the superheated water vapor is preferably 200° C. to 450° C. When the temperature is lower than 200° C., the chromium concentrations of the two metal layers of the chromium-containing metal layer 14 do not change, and the decrease in heat-resistant peel strength cannot be suppressed. In addition, the superheated water vapor having a temperature higher than 450° C. is difficult to handle, and requires excessive labor for superheated water vapor treatment.
[0053] The spraying time of the superheated water vapor is preferably 60 seconds or more and 180 seconds or less. When the time is shorter than 60 seconds, the chromium concentration of the two metal layers of the chromium-containing metal layer 14 does not change, and the decrease in heat-resistant peel strength cannot be suppressed. In addition, when the time is longer than 180 seconds, the productivity of the flexible substrate 10 decreases.
[0054] exist Figure 3 TEM element mapping measurements of the flexible substrate 10 before and after the superheated water vapor treatment are shown in FIG. Figure 2 The width of the hatched lines in the circle indicates the amount of each element. That is, the narrow hatched lines have more elements than the wide hatched lines, which means that the volume percentage of the elements is high. Figure 3 (A) Figure 3 (B) shows the distribution of chromium before and after superheated steam treatment. Figure 3 (C) Figure 3 (D) shows the distribution state of copper element before and after the superheated water vapor treatment.
[0055] like Figure 3 As shown in (B), in the early stage of the superheated water vapor treatment, the chromium element is uniformly distributed in the chromium-containing metal layer 14. In the later stage of the superheated water vapor treatment, the chromium element is more present in the first metal layer 14a of the chromium-containing metal layer 14, and the chromium element in the second metal layer 14b is less than that in the first metal layer 14a.
[0056] like Figure 3As shown in (D), in the early stage of the superheated water vapor treatment, the copper element is uniformly present in the base copper layer 15 and the copper conductor layer 13. In the later stage of the superheated water vapor treatment, the copper element diffuses into the second metal layer 14b, but the copper does not diffuse into the first metal layer 14a.
[0057] By performing the superheated water vapor treatment, the weight percentage of chromium in the first metal layer 14 a is higher than that in the second metal layer 14 b as described above, thereby suppressing the diffusion of the copper element and suppressing the decrease in the heat-resistant peel strength.
[0058] The thickness of the first metal layer 14a (in Figure 1 The distance between the top and bottom of the paper is determined by the temperature and time of the superheated steam treatment. For example, the diffusion of copper elements can be suppressed as long as it is above 20 angstroms.
[0059] (Example)
[0060] Hereinafter, the present invention will be described with reference to examples and comparative examples. It should be noted that the flexible substrate 10 of the present invention is not limited to the following examples at all.
[0061] (Example 1)
[0062] As the polyimide film 11, Kapton (registered trademark) 100EN film manufactured by Toray DuPont was used. On both sides of the polyimide film 11, a 150 angstrom chromium-containing metal layer 14 was formed by sputtering, and a 200 nm base copper layer 15 was formed by overlapping the chromium-containing metal layer 14. These chromium-containing metal layers 14 and base copper layers 15 formed a base metal layer 12. In addition, in Example 1, the chromium ratio of the chromium-containing metal was 20 weight percent, and the remaining metals were almost all nickel. On the base metal layer 12, an 8 μm copper conductor layer 13 was formed by copper electroplating. Then, after spraying superheated water vapor at 300°C for about 120 seconds, the flexible substrate 10 was obtained by cooling the substrate to room temperature.
[0063] The thickness of the first metal layer 14a in the flexible substrate 10 was measured. In addition, a 1 mm wide pattern for measuring peel strength was made from the flexible substrate 10 using a ferric chloride etching solution. Then, the initial peel strength of the flexible substrate 10 was measured. In addition, the flexible substrate 10 was heated to 150°C in the atmosphere and kept for 168 hours, and then the heat-resistant peel strength was measured. Regarding the heat-resistant peel strength, as long as it has a ratio of 75% of the initial peel strength, it is judged to be good. The results are shown in Table 1.
[0064] In Example 1, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0065] (Example 2)
[0066] The conditions were the same as those in Example 1 except that the chromium content of the chromium-containing metal layer 14 was 40 weight percent.
[0067] In Example 2, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0068] (Example 3)
[0069] The conditions were the same as those in Example 1 except that the chromium content of the chromium-containing metal layer 14 was 100 weight percent.
[0070] In Example 3, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0071] (Example 4)
[0072] The conditions were the same as those in Example 1 except that the film thickness of the metal layer 14 containing chromium was 75 angstroms. The measurement results are shown in Table 1.
[0073] In Example 4, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0074] (Example 5)
[0075] The conditions were the same as those in Example 1 except that the film thickness of the metal layer 14 containing chromium was 300 angstroms. The measurement results are shown in Table 1.
[0076] In Example 5, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%, which was a good result that the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0077] (Example 6)
[0078] The conditions were the same as those in Example 1 except that the temperature of the superheated water vapor was 200° C. The measurement results are shown in Table 1.
[0079] In Example 6, the initial peel strength was 510 N / m, the heat-resistant peel strength was 400 N / m, and the strength retention rate was 78.4%. That is, although the heat-resistant peel strength decreased, a good result of about 78% of the initial peel strength was obtained.
[0080] (Example 7)
[0081] The conditions were the same as those in Example 1 except that the temperature of the superheated water vapor was 350°C. The measurement results are shown in Table 1.
[0082] In Example 7, the initial peel strength was 510 N / m, the heat-resistant peel strength was 500 N / m, and the strength retention rate was 98.0%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0083] (Example 8)
[0084] The conditions were the same as those in Example 1 except that the temperature of the superheated water vapor was 450°C. The measurement results are shown in Table 1.
[0085] In Example 8, the initial peel strength was 510 N / m, the heat-resistant peel strength was 510 N / m, and the strength retention rate was 100%. That is, a good result was obtained in that the heat-resistant peel strength and the initial peel strength did not change.
[0086] (Example 9)
[0087] The same conditions as in Example 1 were used except that the polyimide film 11 was UPILEX (registered trademark) 25SGA manufactured by Ube Industries, Ltd. The measurement results are shown in Table 1.
[0088] In Example 9, the initial peel strength was 550 N / m, the heat-resistant peel strength was 450 N / m, and the strength retention rate was 81.8%. That is, a good result was obtained in which the heat-resistant peel strength and the initial peel strength were almost unchanged.
[0089] (Comparative Example 1)
[0090] The conditions were the same as those in Example 1 except that the superheated water vapor treatment was not performed. The measurement results are shown in Table 1.
[0091] In Comparative Example 1, the initial peel strength was 510 N / m, the heat-resistant peel strength was 350 N / m, and the strength retention rate was 68.6%. That is, the heat-resistant peel strength was lower than the initial peel strength.
[0092] (Comparative Example 2)
[0093] The conditions were the same as those in Example 1 except that the chromium content of the chromium-containing metal layer 14 was 7 weight percent.
[0094] In Comparative Example 2, the initial peel strength was 510 N / m, the heat-resistant peel strength was 300 N / m, and the strength retention rate was 58.8%. That is, the heat-resistant peel strength was lower than the initial peel strength.
[0095] (Comparative Example 3)
[0096] The conditions were the same as those in Example 1 except that the film thickness of the metal layer 14 containing chromium was 30 angstroms. The measurement results are shown in Table 1.
[0097] In Comparative Example 3, the initial peel strength was 510 N / m, the heat-resistant peel strength was 200 N / m, and the strength retention rate was 39.2%. That is, the heat-resistant peel strength was lower than the initial peel strength.
[0098] (Comparative Example 4)
[0099] The polyimide film 11 was UPILEX (registered trademark) 25SGA manufactured by Ube Industries, Ltd. and the conditions were the same as those in Example 1 except that the superheated water vapor treatment was not performed. The measurement results are shown in Table 1.
[0100] In Comparative Example 4, the initial peel strength was 600 N / m, the heat-resistant peel strength was 300 N / m, and the strength retention rate was 50.0%. That is, the heat-resistant peel strength was lower than the initial peel strength.
[0101] [Table 1]
[0102]
Claims
1. A method for manufacturing a flexible substrate, characterized in that: The manufacturing method of the flexible substrate comprises: forming, on the surface of the polyimide film, a base metal layer including a metal layer containing chromium in contact with the polyimide film; The step of forming a copper conductor layer by overlapping the base metal layer; as well as The step of heating the polyimide film, the base metal layer, and the copper conductor layer by a predetermined heating method so that the chromium-containing metal layer has a structure consisting of a first metal layer in contact with the polyimide film and a second metal layer located on the first metal layer in an overlapping manner, The weight percentage of chromium in the first metal layer is greater than the weight percentage of chromium in the second metal layer.
2. The method for manufacturing a flexible substrate according to claim 1, wherein: The heating method is a superheated water vapor treatment in which superheated water vapor is sprayed toward the polyimide film, the base metal layer, and the copper conductor layer.
Citation Information
Patent Citations
Formation of conductor layer on polyimide insulation layer
JP1990098994A
Double layer copper polyimide substrate
JP2007318177A
Metal-clad polyimide resin substrate with excellent thermal aging resistance characteristics
WO2010098236A1